Swallowing analysis in hemi‐tongue reconstruction using motor‐innervated free flaps: A cine‐magnetic resonance imaging study. Issue 5 (25th February 2023) - Kim, Young Chul; Lee, Seok Joon; Park, Hojin; Choi, Young Jun; Jeong, Woo Shik; Lee, Yoon Se; Choi, Kyoung Hyo; Oh, Tae Suk; Choi, Jong Woo
Abstract: Background: This study aimed to explore the outcomes of motor‐innervated free flaps in hemi‐tongue reconstruction by assessing the tongue mobility through midsagittal images from cine‐magnetic resonance imaging. Methods: In this retrospective study, 47 patients who underwent tongue reconstruction following hemi‐glossectomy and 10 control subjects without any surgical history were included. Patients were classified into two groups: the motor and no‐motor innervation group. Various spatial parameters related to tongue mobility that were acquired from midsagittal sections were compared during consecutive swallowing phases. Results: Overall, the motor group showed improved functional swallowing scale compared with the no‐motor group. In case of tongue base resection, the motor group showed improved mobility of the tongue base during pharyngeal phase, whereas the no‐motor group showed increased laryngeal elevation for compensatory movement. Conclusion: The tongue reconstruction with motor‐innervated free flaps may facilitate swallowing capacity in patients with a hemi‐tongue defect combined with tongue base resection.